Casopitant: a novel NK1-receptor antagonist in the prevention of chemotherapy-induced nausea and vomiting - Christina Ruhlmann; Jørn Herrstedt (Dove Medical Press, 2009)
Christina Ruhlmann, Jørn HerrstedtOdense University Hospital, Department of Oncology, Odense, DenmarkAbstract: Chemotherapy-induced nausea and vomiting (CINV) are among the most feared and distressing symptoms experienced by patients with cancer. The knowledge of the pathogenesis and neuropharmacology of CINV has expanded enormously over the last decades, the most significant discoveries being the role of 5-hydroxytryptamine (5-HT)3- and neurokinin (NK)1 receptors in the emetic reflex arch. This has led to the development of two new classes of antiemetics acting as highly selective antagonists at one of these receptors. These drugs have had a huge impact in the protection from chemotherapy-induced vomiting, whereas the effect on nausea seems to be limited. The first NK1 receptor antagonist, aprepitant, became clinically available in 2003, and casopitant, the second in this class of antiemetics, has now completed phase III trials. This review delineates the properties and clinical use of casopitant in the prevention of CINV.Keywords: casopitant, GW679769, NK1 receptor antagonist, chemotherapy, emesis